Ferroelectricity and carrier dynamics in multidimensional organic-inorganic hybrid lead halide perovskites - Zhang, Qiannan (Nanyang Technological University, 2021)
The organic-inorganic hybrid lead halide perovskite fever stems from a rapid rise in power conversion efficiency of perovskite solar cells (PSC) to more than 25 % within 10 years, which makes them comparable to commercial silicon solar cells. Apart from these conventional 3D perovskites, the emergence of Ruddlesden-Popper (RP) hybrid perovskites was inspired from its remarkable moisture stability by the incorporation of hydrophobic cations as well as its “soft” multidimensional layered structure through chemical engineering. The unique “soft” structure provides an opportunity to explore their ferroelectric properties, which could potentially have a strong impact on carrier dynamics due to the presence of spontaneous polarizations in nanodomains and thus suppress recombination loss in solar cells. However, the structure-function properties and the factors determining the tuning of ferroelectric properties in RP perovskites are still open questions. Besides, in the application of RP perovskite-based LEDs, mechanisms for the detrimental bottleneck “efficiency roll-off” are still unclear and under debate. Therefore, the main focus of this thesis is to investigate the structure-function relations affecting the ferroelectric properties and to uncover the mechanisms behind “efficiency roll-off” from the view of electric field dependent carrier dynamics in RP perovskites. Piezoresponse force microscopy and time-resolved transient reflection spectroscopy are the main tools for these studies. Importantly, our findings disclose composition engineering as an approach to tune the ferroelectric properties and exciton coupling as the key to electrically control the quenching phenomenon, which provides fresh opportunities to unlock new functionalities for perovskite optoelectronic devices.